Optical properties of ionized donor-bound excitons confined in strained wurtzite ZnO/MgxZn1−xO quantum dots*Project supported by the National Natural Science Foundation for Young Scientists of China (No. 11102100), the Program for New Century Excellent Talents in Fujian Province University (No. JA14285) and the Program for Young Top-Notch Innovative Talents of Fujian Province of China. (March 2015) - Zheng, Dongmei; Wang, Zongchi; Xiao, Boqi
Abstract Within the framework of the effective-mass approximation and the dipole approximation, considering the three-dimensional confinement of the electron and hole and the strong built-in electric field (BEF) in strained wurtzite ZnO/Mg0.25Zn0.75O quantum dots (QDs), the optical properties of ionized donor-bound excitons (D+, X) are investigated theoretically using a variational method. The computations are performed in the case of finite band offset. Numerical results indicate that the optical properties of (D+, X) complexes sensitively depend on the donor position, the QD size and the BEF. The binding energy of (D+, X) complexes is larger when the donor is located in the vicinity of the left interface of the QDs, and it decreases with increasing QD size. The oscillator strength reduces with an increase in the dot height and increases with an increase in the dot radius. Furthermore, when the QD size decreases, the absorption peak intensity shows a marked increment, and the absorption coefficient peak has a blueshift. The strong BEF causes a redshift of the absorption coefficient peak and causes the absorption peak intensity to decrease remarkably. The physical reasons for these relationships have been analyzed in depth.